Improving the Energy Efficiency of Buildings. The Project MARIE - Correia-da-Silva, José Júlio (2014)
Project MARIE - Mediterranean Building Rethinking for Energy Efficiency Improvement is a strategic project from the European Union in the scope of the MED Program. The project aims to promote building energy efficiency in the Mediterranean region and overcome the mains barriers to large scale improvement, trough the development of a common strategy adaptable to each country/region specifications, in the framework of EU building energy efficiency policies. The project counts with the participation of 22 institutions from 9 different MED countries: Portugal, Spain, Italy, Slovenia, Montenegro, Greece, Malta, and Cyprus. It has started in April 2011 and it schedule to last until the end of 2014. This article presents a description of the Project MARIE, its stage of development, and also the results achieved in the first third of the project; in order to share the gained knowledge with the scientific and technical community.